(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2024)
Background. The investigation of the degradation of organic dyes influenced by chemical and physical factors is important for the study of the stability of paints on the canvases of paintings and fabrics. Comparison of the effect of different types of oxidants on the optical and electrochemical characteristics of paints remains a relevant issue, which will allow choosing the optimal method of studying the degradation of a certain type of dye, and also help to estimate the minimum time of its decomposition. Differences in the chemical structure determine the different resistance of dyes to the different types of oxidants. It is considered expedient to compare chemical, electrochemical and photochemical methods of oxidation of two classes of dyes in order to optimize methods of studying of their degradation. It was investigated eosin Y (EOS Y) and alizarin red S (ARS), which are used in artistic paints and dyes for fabrics and are the examples of the xanthene and anthraquinone types. The aim of this work was to compare chemical, voltammetric and photochemical methods of oxidation of dyes of different types, which are included in the composition of paints, namely eosin Y and alizarin red S in aqueous solutions to choose the optimal method of studying of their degradation. Methods. Spectrophotometry and cyclic voltammetry were used in the work; photochemical oxidation of dyes was carried out under the exposure to sunlight. Results. The dependences of the degree of the decomposition of EOS Y and ARS on the time of contact of the dye with Fenton’s reagent were obtained. EOS Y decomposes by 87% in the first two min, in 30 min 90% of the dye is decomposed. ARS decomposes by 25% in the first few min, and by 70% in 30 min. Cyclic voltammograms of EOS Y and ARS solutions on a carbon electrode were obtained. Electrochemical oxidation of EOS Y occurs irreversibly in one stage in acidic and neutral medium. ARS is oxidized reversibly according to the first stage and irreversibly according to the second one in an acidic medium at pH 2-3. The double dissociated form of ARS at pH > 4 is oxidized at lower potentials than its molecular form. EOS Y decomposes most intensively during the first day of exposure (degree of decomposition is 56,4%) under the exposure to sunlight. In 36 days of contact with sunlight the dye decomposes by 93%. In contrast the anthraquinone dye ARS decomposes by only 9,6% in 21 days which indicates its higher photostability. Conclusions. Xanthene dye EOS Y is more efficiently oxidized by the chemical method with Fenton’s reagent and under the exposure to sunlight compared to the anthraquinone dye ARS, which has a condensed aromatic structure, which makes it more resistant to the oxidants. Although chemical oxidation is more effective for both dyes, the degree of decomposition of EOS Y is 1,5 times greater than that of ARS (78,4 and 51,5%, respectively). Both dyes are oxidized on the surface of the carbon electrode. Using the method of cyclic voltammetry, it was established that in an acidic medium, EOS Y is oxidized in one stage, and ARS - in two stages. For the investigated dyes, the chemical method using spectrophotometric detection makes it possible to detect n∙10-6 mol/l of the corresponding dye in the solution. The method of cyclic voltammetry can be used to study the degradation of both types of the dyes but for the anthraquinone dye ARS, the lower limit of detection 3,3∙10-5 mol/l is obtained compared to EOS Y.